Chronic obstructive pulmonary disease treated with inhaled medium- or high-dose corticosteroids: a prospective and randomized study focusing on clinical efficacy and the risk of pneumonia - Cheng SL; Su KC; Wang HC; Perng DW; Yang PC (Dove Medical Press, 2014)
Shih-Lung Cheng,1,2 Kang-Cheng Su,3 Hao-Chien Wang,4,* Diahn-Warng Perng,3,* Pan-Chyr Yang4 1Department of Internal Medicine, Far Eastern Memorial Hospital, New Taipei City, 2Department of Chemical Engineering and Materials Science, Yuan Ze University, Zhongli City, Taoyuan County, 3Department of Chest Medicine, Taipei Veterans General Hospital, Taipei, 4Department of Internal Medicine, National Taiwan University Hospital, Taipei, Taiwan *These authors contributed equally to this work Purpose: Complications of pneumonia development in patients with chronic obstructive pulmonary disease (COPD) receiving inhaled corticosteroid (ICS) therapy have been documented. The aim of this study was to focus on clinical efficacy and the incidence of pneumonia between COPD patients receiving medium and high doses of ICS. Patients and methods: This prospective, randomized study included COPD patients identified from three tertiary medical centers from 2010 to 2012. The patients were randomized into two groups: high dose (HD; fluticasone 1,000 µg + salmeterol 100 µg/day) and medium dose (MD; fluticasone 500 µg + salmeterol 100 µg/day). Lung function with forced expiratory volume in 1 second (FEV1), forced vital capacity, and COPD-assessment test (CAT) were checked every 2 months. The frequency of acute exacerbations and number of pneumonia events were measured. The duration of the study period was 1 year. Results: In total, 237 COPD patients were randomized into the two treatment arms (115 in the HD group, 122 in the MD group). The FEV1 level was significantly improved in the patients in the HD group compared with those in the MD group (HD 103.9±26.6 mL versus MD 51.4±19.7 mL, P<0.01) at the end of the study. CAT scores were markedly improved in patients using an HD compared to those using an MD (HD 13±5 versus MD 16±7, P=0.05). There was a significant difference in the percentage of annual rates in acute exacerbations (HD 0.16 versus MD 0.34, P<0.01) between the two groups. The incidence of pneumonia was similar in the two groups (HD 0.08 versus MD 0.10, P=0.38). Conclusion: COPD patients treated with high doses of ICS had more treatment benefits and no significant increases in the incidence in pneumonia. Higher-dose ICS treatment may be suitable for COPD therapy. Keywords: chronic obstructive pulmonary disease, pneumonia, inhaled corticosteroids